If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(4 + x) = 144 (4 * 4 + x * 4) = 144 (16 + 4x) = 144 Solving 16 + 4x = 144 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 4x = 144 + -16 Combine like terms: 16 + -16 = 0 0 + 4x = 144 + -16 4x = 144 + -16 Combine like terms: 144 + -16 = 128 4x = 128 Divide each side by '4'. x = 32 Simplifying x = 32
| 9(4x-5r)= | | 80=2/3-3/5 | | 80=1/3-2/5 | | 3x+3x+1= | | 1x+5y=8 | | X+21.5=-14.4 | | 3x+1=(-17) | | 2h+6=12 | | 80=2/3-2/5 | | 3(x+1)=(-17) | | 2x+3x-(x+5y)= | | 80=2/3-2/15 | | 3x+3x+1=(-17) | | x/7-4=51 | | -(x^2)-100x+375=0 | | (4x-12)/6 | | (4x^5)(3x^8)=9 | | 4/12=n/42 | | cos30=5/c | | 5cos(2x-3)=1 | | 14x+(-9y)+(-7x)+6y= | | 3/5x-7/15=4/3 | | 16x=-4(6-x) | | 7m+2n=6n-5 | | w^2-4w= | | 8*3/4=6 | | (7x+3)(x+5)=0 | | (5-v)(2v-1)=0 | | 7+2x=7x-18 | | -6+(-4)+3(-8)= | | =-5x+2-3x-6 | | 4p(-7p+13)=6-(10p-4) |